Civic engagement: Digital activism of university students in Malang amidst covid-19 pandemic - Nurbani Yusuf; Arif Prasetyo Wibowo (Jurnal Civics: Media Kajian Kewarganegaraan, 2021)
This research discusses: a) The digital activism of university students in Malang amidst COVID-19 pandemic, b) The media used by the students to run the digital activism amidst the COVID-19 pandemic, and c) Political movements carried out by the students amidst the COVID-19 pandemic. This present research implemented qualitative approach using case study to describe the findings of phenomena that occur in the field. Taking concern on the discussed issue in the research, the case study method required a number of field data that are contextual and actual. Meanwhile, the results of this research found that the use of digital space as a place to carry out activism activites is one form of social change. It is observed that students' activism in the midst of the COVID-19 outbreak has changed pattern. The change was a move from conventional, mass gathering, into online using a variety of platform. This change in carrying out students' political movement has succeeded in attracting public attention which resulted in the success of political movements and gathering and amplifying "attention" on certain social issues.